Using Risk Analysis and Patterns to Tailor Software Processes - Hartmann, Júlio; Fontoura, Lisandra M.; Price, Roberto T. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2005: Anais do XIX Simpósio Brasileiro de Engenharia de Software, 2005)
This paper discusses an approach to tailor software development processes and methodologies based on organizational patterns and risk criteria. The purpose of the approach is to adapt an organizational pattern language to the context of a given project. The most suitable organizational patterns to the requirements of the project should be chosen analyzing the risks and the criticality context of the project. Organizational patterns which describe preventive techniques for the identified risks can be selected by a systematic retrieval system. The process designer evaluates the selected patterns and takes the adaptation decisions. PMT-Tool, a tool that supports the approach, is briefly described.